Nietzschės domestikacija: tarp Elisabeth'ės mito ir Kaufmanno interpretacijos. - Andrijauskas, Jokūbas (Problems / Problemos, 2025)
Friedrich Nietzsche's political philosophy, permeated by aristocratic radicalism, challenges contemporary values, but is often smoothed out or depoliticised. In this text, I analyse two tactics by which this is accomplished in Nietzsche's research. I analyse the myth of Elisabeth Förster -- Nietzsche's alleged falsification of texts as a factually unsubstantiated projection, and Walter Kaufmann's apolitical interpretation of Nietzsche's philosophy as meaningfully limited. I show that, despite Nietzsche's anti-antisemitism and critique of German culture, his aristocratic radicalism justifies a hierarchical, brutal politics. I argue that both Elisabeth's myth and Kaufmann's interpretation can be understood as a specific form of interpretation, as domestication. I argue that these forms of domestication contradict the pursuit of 'harsh truths' which is essential to Nietzsche's philosophy. Lastly, I claim that domestication is a serious obstacle to a reconstruction of Nietzsche's political thought.